Experimental study on the effect of prefabricated fissures on the creep mechanical properties and acoustic emission characteristics of sandstone under uniaxial compression - Yu, Huaichang; Wang, Guanqiang; Zhang, Zhongyu; Niu, Rui; Cheng, Guangli (Frontiers in Earth Science, 2022)
This study investigates the effects of prefabricated cracks on the creep mechanical strength and AE characteristics of sandstone. Under the same test conditions, indoor uniaxial compression creeps acoustic emission tests were performed on intact and artificially fissured sandstone specimens using an RLJW-2000 microcomputer to control rock rheometer and PCI-Ⅱ acoustic emission tester. The variation characteristics of strain, long-term strength, number of AE events, AE ringing count, AE energy, and RA value of the two specimens were then analyzed to determine the effect of prefabricated fissures on the creep mechanical properties and acoustic emission characteristics of sandstone. The results show that, under the same stress level, the instantaneous strain, creep strain, and total strain of the prefabricated fissures specimen is larger than the corresponding values of the intact specimen. The prefabricated fissures have the most significant influence on the creep strain of the specimen, followed by the total strain. The fissures have the least influence on the instantaneous strain of the specimen. Furthermore, the long-term strength of the prefabricated fissures specimen is only 37.5% of the long-term strength of the intact specimen. Due to the influence of the prefabricated fissures, the long-term strength of the sandstone is significantly reduced. In engineering practice, fissures should be noted and analyzed for the potential failure of a formation. Also, as the stress level increases, the number of AE events of the specimen increases. The number of AE events and cumulative AE events generated by the prefabricated fissure specimens at various stress levels is significantly higher than the corresponding values of the intact specimen. The maximum ringing count of the prefabricated fissure specimen is 7.3 times that of the intact specimen, and the maximum AE energy is 3.8 times that of the intact specimen. The cumulative AE ringing count is 1.5 times that of the intact specimen, and the cumulative energy is 4.5 times that of the intact specimen. The prefabricated fissures significantly affect the maximum AE ringing count, maximum AE energy, cumulative AE ringing count, and cumulative AE energy of the specimen.